2017
DOI: 10.11648/j.am.20170601.11
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Some Mechanical Properties of Papercrete Concrete

Abstract: Abstract:This study presents an experimental approach for the use of Papercrete for construction. Green materials are now the preferred material for construction since they are capable of lighter weight and affordable. Based on recent studies, alternative building materials are cost effective, light weight when dry, and efficient to use. This study started from referring different literatures concerning the topic and related ideas up to conceptualization and design of the trial ratio to be used in testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
(5 reference statements)
1
3
0
Order By: Relevance
“…Adding a higher percentage of sawdust decreases the compressive strength. Similar trends were observed in literature [16][17][18][19][20] for a replacement of 2% and higher with sawdust. Since saw dust is finer than the pumice and fills the gap between the particles and increases bonding strength at the microscopic level.…”
Section: Effect Of Compressive Strength On Hcbs Using Sawdustsupporting
confidence: 91%
See 1 more Smart Citation
“…Adding a higher percentage of sawdust decreases the compressive strength. Similar trends were observed in literature [16][17][18][19][20] for a replacement of 2% and higher with sawdust. Since saw dust is finer than the pumice and fills the gap between the particles and increases bonding strength at the microscopic level.…”
Section: Effect Of Compressive Strength On Hcbs Using Sawdustsupporting
confidence: 91%
“…Due to the smaller particle size, highwater absorption and an increase in weight of the blocks are to be expected. It is observed that the curve for pumice shows a gradation gap between the particle size, which influences the strength of HCBs [17]. It is also observed the particles size between 0.6 and 0.3.…”
Section: Properties Of Materialsmentioning
confidence: 76%
“…Papercrete was rediscovered in the 1980s, independently by Eric Patterson and Mike McCain (they called it respectively "padobe" and "fibrous cement"). It is recognized as an environment-friendly material due to significant recycled content and its ability to reduce the dead load for the main structure [6,7]. The manufacturing process of paper generally produces a large amount of solid waste.…”
Section: Of 11mentioning
confidence: 99%
“…Other gains in paperbricks are lightweight, low energy consumption during the production process, low cost, and ease of transportation as compared to conventional bricks. Paperbricks are produced by the mixture of cement, paper pulp, sand, and other forms of additives in varying proportions towards satisfying certain specifications 12 . Paperbricks have little patronage for building purposes owing to the low strength acclaimed to them and high water absorption tendency since paper is susceptible to water assimilation.…”
Section: Introductionmentioning
confidence: 99%